Euthanasia and assisted suicide: lessons from Belgium - Jones, David Albert; Gastmans, Chris; MacKellar, C. (Calum) (Cambridge Cambridge University Press, 2017)
Examining the evidence from Belgium – one of only five countries where euthanasia is practised legally – an international panel of experts considers the implications of legalised euthanasia and assisted suicide. Looking at the issue from an international perspective, the authors have written an invaluable in-depth analysis of the ethical aspects of this complex area. The discussion forms a solid foundation for informed debate about assisted dying. With contributors from a broad range of disciplines, this book is ideal for students, academics, legislators and anyone interested in legal, medical, social and philosophical ethics. A vital and timely examination of a growing phenomenon and one of the most challenging ethical questions of our time.
Appendix III The Belgian Act on Euthanasia of 28 May 2002 (unofficial translation)
Keywords: 241.63*4 -- Theologische ethiek: euthanasie